Contemporary families and digital practices : which adjustments for which norms ? - Balleys, Claire; Martin, Olivier; Jochems, Sylvie (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2018)
Research Framework : Sociological knowledge about the link between digital practices and family life still needs developing. It is within this context, this journal issue and introductory article explore how marital negotiations and parent-child relationships are being transformed by these digital practices, forms of surveillance mediated by these technologies or, conversely, new ways in which autonomy is attained, the balance between peer and familial socialisation, as well as the connection between gender roles and the ways in which these technologies are used by couples and families. Objectives : This introductory article is designed to present the current state of research on these topics and critically examine the corpus of articles included in this issue.Methodology : Through a review of the literature, we situate this special issue within a broader context of research that, for nearly twenty years, at the intersection of work on the family and work on communication technologies and the internet.Results : In the first section, we suggest that this field of research is yet to be developed. In the following sections, we will show how the articles in this themed issue largely demonstrate that family digital practices reflect current social norms, as well as the tensions these norms may create. Although this analysis is not new (Pasquier, 2018), it is refined by the multiplicity of actors, discourses, and methodologies. Conclusions : As a result of the evaluation and selection of the articles, this themed issue is intended to give a voice to sociologists influenced by a relationist approach and a constructivist language. These articles deal with intimacy and fall within the framework of the sociology of everyday life, taking a close look at ordinary practices. Technologicaly deterministic analyses (Jauréguilberry and Proulx, 2011) are therefore less present. Scholars interested in these topics will find that much remains to be done, and the constant evolution of these practices and technologies ensures that there will always be new questions to address.Contribution : This themed issue contributes to the dialogue between various sociological studies of the individual and his or her relationship to norms, where some believe that the norms govern the individual (structuralism), while others believe that the individual negotiate and co-creates the norms regulating these 'good practices' (pragmatism, interactionism). Moreover, this introductory article will provide a short but necessary survey of French-language sociological knowledge about families in the digital era   –   a way to remind ourselves and our readers of the Foucauldian idea that scientific works about a research topic are not neutral.